The Potensi Mikroalga Laut, Chlorella vulgaris, dalam Menghasilkan Listrik - Qori Atur R. Suhada; Aditya Indra Gunawan; Tiwi Sartika; Hasna Labib Lathifah; Marsya Naranissa Puteri; Maya Amini Sukma; Nadilla Suci Nugraha; Rosi Ainin Faqihah; Tiara Zahira (Jurnal Biodiversitas dan Bioteknologi, 2024)
Electrical energy is energy that comes from an electric charge that creates a static electric field or the movement of electrons in electrical conductors or ions (positive or negative) in liquids or substances in the form of gases. One of the sources of renewable electrical energy can be obtained from marine microalgae through the process of photosynthesis, called Biophotovoltaics. The electrical energy produced by these marine microalgae can be channeled to power electronic devices. Chlorella vulgaris is a photosynthetic microorganism that can be used in biophotovoltaics systems. The purpose of this observation is to utilize microalgae as a renewable energy source and to develop the potential of microalgae, especially green algae. The method used is to create a Biophotovoltaics system utilizing 2 glass tubes filled with microalgae cultures which are connected to an electrical circuit using aluminum and steel electrodes. The experiments carried out produced electricity of 2.5V from 2 liters of microalgae culture that had previously been made. The amount of electric voltage obtained from the microalgae is strongly influenced by the biomass it produces during photosynthesis.